Minutes of the 2nd Meeting of BRAC University Board of Trustees (BoT) - Board of Trustees (BoT), BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of the Minutes of the 1st Meeting of Board of Trustees. 2. Review of the progress of decisions of the 1st Meeting of Board of Trustees. 3. Approval of the Minutes of 1st and 2nd Meeting of BRACU Syndicate. 4. Approval of the Minutes of 41st and 42nd Meetings of Academic Council (AC). 5. Approval of the Minutes of the 1st Meeting of Finance Committee. 6. Approval of the Proposed Budget for 2011-2012 of BRACU. 7. Approval of the Minutes of the 1st Meeting of Disciplinary Committee. 8. Approval of the Minutes of the 1st Faculty Appointment Committee Meeting. 9. Approval of the Minutes of the 1st Staff Appointment Committee Meeting. 10. Preparation of 7th Convocation. 11. Progress on Permanent Campus. 12. Appointment of the Treasurer,BRACU. 13. Miscellaneous: 13.1 Increasing Hostel Accommodation for Students. 13.2 Review of Statute, Organogram and Terms of Conditions of Service of BRACU. 13.3 Reorganization of Institutes and Schools. 13.4 Establishment of Center for Entrepreneurship Development (CEO). 13.5 Establishment of Center for Climate Change and Environmental Research (C3ER). 13.6 Space Problem of BRACU. 13.7 Discussion on Gender issues. 13.8 MOUs Signed since the formation of BoT.